MANAJEMEN STRATEGIK INSTITUT AGAMA ISLAM NEGERI (IAIN) SYEKH NURJATI CIREBON - Ahmad Fauzi; Syibli Maufur (JIEM (Journal of Islamic Education Management), 2019)
Profesionalization of Education Management is a strategic sector in developing quality of education as an effort for improving the human resource in the era of millennium developmental goals. On the other hand, Indonesia has low competitiveness caused by low of quality of human resource. Whereas education and educator, educational staff, and institutional management are spearhead in developing quality of human resource. In general, the objective of this research is to formulate a calculation method of performance accountability as an application of principles and theory of strategic management on education activity in IAIN Syekh Nurjati. The method used in this research is non-experimental quantitative research, namely analytical descriptive method. The conclusion of this research are (1) Calculation method of performance accountability used by IAIN Syekh Nurjati refer to recent rules. From point of view of strategic management theory, the two models have a low analysis accuracy. (2) Performance accountability of activity, program, and policy in institutional management of IAIN Syekh Nurjati Cirebon, all of them are very successful category. (3) Formulation of calculation method of perfomance accountability of IAIN Syekh Nurjati refer to theory of strategic management which in line with characteristics of Strategic Planning of IAIN Syekh Nurjati 2015-2019 and is inaccordance with UNESCO new paradigm of higher education institution (World Declaration on Higher Education for the Twenty First Century: Vision and Action) which is made as reference of new concept of higher education institution development in Indonesia. (4) In management of IAIN Syekh Nurjati Cirebon, it’s relation are very strong, strong, very strong, and very strong. Further more there are several recommendations, namely (1) On calculation of perfermance accountability for IAIN Syekh Nurjati needed calculation of degree of relationship or influence between policy variables, program, and activity as variables of strategic implementation. (2) Phase of model of strategic management should be agreed by concerning people and decided by people who have jurisdiction to be made as reference and together commitment. (3) For certain faculties, institute, or educational institution at local, regional, or national level it is necessary to appoint a strategic management commitee responsible for developing “Statement of Best Practices” Key Words: Management, Accountability, Performance